2010
DOI: 10.3109/17538157.2010.528637
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring systems for the support of home care

Abstract: In this article, the design of a system for the ambient, unobtrusive and automatic monitoring of Activities of Daily Living (ADL) is described. In the context of the growing imbalance between (potentially young) caregivers and (most often older) people receiving care, technical monitoring systems may help to organise care more efficiently and to identify degrading abilities very early to trigger preventive measures. To improve the acceptance of the system described in this article, the selection process of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A specific attention has then been given also by elderly to the ability to handle medications. This result is supported by several references in the literature [13,19,24,34] users mentioned the need to prevent potential risks related to environmental factors. Factors suggested to monitor were for instance: fire detection, taps opened, smoke detection, wet floor, temperature, and gas leaking.…”
Section: Focus Group Resultssupporting
confidence: 74%
“…A specific attention has then been given also by elderly to the ability to handle medications. This result is supported by several references in the literature [13,19,24,34] users mentioned the need to prevent potential risks related to environmental factors. Factors suggested to monitor were for instance: fire detection, taps opened, smoke detection, wet floor, temperature, and gas leaking.…”
Section: Focus Group Resultssupporting
confidence: 74%
“…Hence, we focus on mostly ambient-sensor-based works in this survey. However, some research works that utilized both wearable and ambient sensors have been reported here, as shown in Table 9 [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ].…”
Section: Ambient Sensors In Elderly Carementioning
confidence: 99%
“…35,[155][156][157][158] Seven studies reported successful outcomes of telemonitoring. 106,[159][160][161][162][163][164] Mobile computing devices for information sharing, decision making, communication, and developing social capital were developed. [165][166][167][168][169][170][171] Technologically supported systems for self-management and home-therapy techniques were also reported.…”
Section: Treatment-related (Five Studies)mentioning
confidence: 99%